2001
DOI: 10.1159/000051154
|View full text |Cite
|
Sign up to set email alerts
|

Disease Knowledge and Attitudes toward Predictive Testing and Prenatal Diagnosis in Families with Machado-Joseph Disease from the Azores Islands (Portugal)

Abstract: Objective: Machado-Joseph disease (MJD) reaches its highest prevalence world-wide in the Azores, thus constituting a public health problem in these islands. The aim of the study was thus to (1) determine the level of knowledge about the disease; (2) estimate the expected level of request for predictive testing, and (3) analyse the intentions of at-risk individuals concerning their reproductive decisions. Methods: A questionnaire on these points was distributed to 42 affected and 36 at-risk individuals. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…A longterm follow-up is offered to all testees, as part of the test procedure. In the Azores, the PT and GC program has been conducted since 1996 by a local multidisciplinary team (Lima et al, 2001;Gonzalez et al, 2004). A component of this program has the main purpose of evaluating, in molecularly confirmed carriers of the MJD mutation, the psychological well-being, the individual and familial representations of the disease, as well as the family dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A longterm follow-up is offered to all testees, as part of the test procedure. In the Azores, the PT and GC program has been conducted since 1996 by a local multidisciplinary team (Lima et al, 2001;Gonzalez et al, 2004). A component of this program has the main purpose of evaluating, in molecularly confirmed carriers of the MJD mutation, the psychological well-being, the individual and familial representations of the disease, as well as the family dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although a worldwide epidemiological representation is presently described for this disorder, some Portuguese clusters are recognized and have received special attention, namely for issues related with genetic counseling (GC) and predictive testing (PT) [6]. Among such clusters are the Azores [7]. …”
Section: Introductionmentioning
confidence: 99%
“…A previous study on the Azorean MJD families conducted by our team which aimed to estimate the expected demand for PT revealed that 83.3% of the individuals at risk intended to perform the genetic test [7]. However, experience with similar disorders, namely Huntington’s disease (HD), has shown that actual behavior is very different from intentions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Acceptance of PND and termination of pregnancy in the presence of the mutation in the fetus was low for this population (Lima et al 2001;Rolim et al 2006).…”
Section: Prenatal Diagnosis For Sca2: What Have We Learned?mentioning
confidence: 83%